A scholarship approach to embedding creativity and sustainability in Marketing Principles curriculum. Issue 2 (May 2018) - von der Heidt, Tania
Highlights: Explicitly deconstructs the six-step SoTL process for a marketing curriculum initiative. Involves upskilling Marketing Principles students in creative problem solving for developing more sustainable product offerings while using principles of marketing planning. Investigates whether CPS can be used effectively by first-year students for collaboratively developing new or improved market offerings positioned on sustainability. Investigates whether students value using CPS for collaboratively developing new or improved offerings positioned on sustainability. Abstract: In business, creativity and innovation can be the difference between success and failure, especially in a world challenged by sustainability issues. Yet creativity and sustainability are rarely discussed with students and seldom appear as part of the formal material in tertiary marketing studies, certainly at the introductory level. This article reports on a curriculum initiative which sought to address this gap in the context of a first-year undergraduate Marketing Principles, multi-cohort course. To help warrant the rigour of the initiative, drawing on the literature, a six-step scholarship of teaching and learning (SoTL) theoretical framework was used to describe the initiative, and to determine its effectiveness. The investigation was informed by a multi-method study comprising descriptive analysis of 323 students' performance scores, content analysis of 59 student groups' preliminary marketing plans, descriptive analysis of 113 students' attitudes (survey), and content analysis of 35 students' post-assessment reflections. The results indicate that sustainability-oriented creativity can be successfully taught and assessed in large, first-year marketing cohorts, provided the curriculum is scaffolded and the teaching team is 'on-board'. Further, viewing teaching and learning initiatives through the SOTL lens is a valuable way for scholarly academics to enhance their intellectual contributions to their schools, to improve student learning experience and outcomes and to help the business school faculty, as well as the marketing discipline. Chinese Abstract: 在商业中, 创造性和创新性决定了成功和失败, 尤其是在面临可持续性问题挑战的世界中. 然而, 我们却很少与学生们讨论创造性和可持续性, 而且创造性和可持续性也很少作为大学教育市场营销学习正式材料的一部分出现 (这当然是入门级水平). 本文章叙述了一项课程设置举措, 该举措力图解决大学本科一年级"市场营销原理"多群组课程背景中的缺口问题. 为了有助于保证该项举措的严谨, 凭借文献著述数据, 使用教与学的学术 (SoTL) 六步式理论框架对该举措进行描述, 并明确了其有效性. 通过多方法研究开展调查, 包括对 323 名学生的表现评分进行描述性分析, 对 59 个学生组的初步市场营销计划进行内容分析, 对 113 名学生的态度进行描述性分析 (调查) 以及对 35 名学生的评估后反思进行内容分析. 结果表明, 只要课程设置有支架支撑且教学团队"就位", 则可在一年级的市场营销学生大群组中成功地教授可持续性导向的创造性, 并进行评估. 此外, 透过 SOTL 视觉观察教与学的举措是非常有价值的方法, 可让学者型的学术人士增加其对学院的学术知识贡献, 改进学生的学习体验和结果, 并有助于商学院教职工以及市场营销这门学科.